Mapping the Level of Earthquake Risk of Holtekamp Bridge at Jayapura Based on Earthquake Data and Microtremor Measurement - Waromi, Doodle Dandy; Khoirullah, Nur; Muslim, Dicky; Mulyo, Agung (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
Holtekamp bridge which is located in Jayapura region between Hamadi and Holtekamp Village inthe Northern part of Papua island. The region constitutes an active earthquake zone with therecurrence frequency and magnitude of the earthquake are relatively high. The region is locatedon an active fault zone. The seismotectonics setting in this region is directly implied to thecalculations of the seismic design for engineering and design purposes on building and non-buildingstructures including Holtekamp bridge in Jayapura city. To recognize a characteristic of theearthquake at the site of interest, the historical earthquakes (background) data surrounding thestudy area. Local microtremor measurements data are analyzed by means of a probabilisticseismic hazard analysis (PSHA). Deterministic seismic hazard analysis (DSHA) using someground-motion models in attenuation relationship equations. In resulting of seismic hazardparameter as represented by peak ground acceleration (PGA), values in earthquake scenario atoperating basis earthquake (OBE), maximum design earthquake (MDE), and maximum credibleearthquake (MCE) conditions. These values are used as a reference to evaluate the complianceof the current technical aspects with the new required design facing the updated seismicityparameters.Keyword : Jayapura, Holtekamp, seismic Hazard Analysis, Peak Ground Acceleration.